Modeling hepatic osteodystrophy in Abcb4 deficient mice - Hochrath, Katrin; Ehnert, Sabrina; Ackert-Bicknell, Cheryl L.; Lau, Yvonne; Schmid, Andrea; Krawczyk, Marcin; Hengstler, Jan G.; Dunn, Jordanne; Hiththetiya, Kanishka; Rathkolb, Birgit; Micklich, Kateryna; Hans, Wolfgang; et al. (Bone, 2013)
Hepatic osteodystrophy (HOD) denotes the alterations in bone morphology and metabolism frequently observed in patients with chronic liver diseases, in particular in case of cholestatic conditions. The molecular mechanisms underlying HOD are only partially understood. In the present study, we characterized the bone phenotypes of the ATP-binding cassette transporter B4 knockout mouse (Abcb4−/−), a well-established mouse model of chronic cholestatic liver disease, with the aim of identifying and characterizing a mouse model for HOD. Furthermore, we investigated the influence of vitamin D on bone quality in this model. The bone morphology analyses revealed reduced bone mineral contents as well as changes in trabecular bone architecture and decreased cortical bone densities in Abcb4−/− mice with severe liver fibrosis. We observed dysregulation of genes involved in bone remodeling (osteoprotegerin, osteocalcin, osteopontin) and vitamin D metabolism (7-dehydrocholesterol reductase, Gc-globulin, Cyp2r1, Cyp27a1) as well as alterations in calcium and vitamin D homeostasis. In addition, serum RANKL and TGF-β levels were increased in Abcb4−/− mice. Vitamin D dietary intervention did not restore the bone phenotypes of Abcb4−/− animals. We conclude that the Abcb4−/− mouse provides an experimental framework and a preclinical model to gain further insights into the molecular pathobiology of HOD and to study the systemic effects of therapeutic interventions.
Gesehen am 22.06.2021